Total Quality Management Based On Conceptions, Principles and Systems for Automotive Materials Purchasing Quality Decision and Management - Bhavani Rohit; J. Rengamani (International Journal of Supply Chain Management, 2018)
In purchasing of automotive materials and parts, Quality Management is makes a difference. This paper firstly discusses with purchasing quality conceptions and purchasing decision making patterns; secondly studies how to apply total quality management principles; and finally the different development levels of purchasing and quality management system. Some innovative thoughts are exhibited to clarify the misunderstanding and ambiguities